Thermo-Optic Nanomaterial Fiber Hydrogen Sensor - Xuhui Zhang; Liang Guo; Xinran Wei; Qiang Liu; Yuzhang Liang; Junsheng Wang; Wei Peng (Nanomaterials)
In the current energy transition procedure, the application prospect of hydrogen as a clean energy material has attracted much attention. However, the widespread use of hydrogen is also accompanied by safety hazards, and how to detect hydrogen safely and efficiently has become a research focus. In this paper, we propose a fiber-optic hydrogen sensor based on the thermo-optic effect and nanomaterials, which combines the unique advantages of fiber-optic grating and platinum-loaded tungsten trioxide and is capable of detecting hydrogen concentration with high sensitivity. The principle of this sensor is to absorb hydrogen molecules by nanomaterials and trigger the exothermic effect, which leads to grating period change and refractive index change in the fiber, thus modulating the resonant wavelength of grating. By monitoring the wavelength drift in real time, the hydrogen concentration can be accurately detected. The experimental results show that the sensor can provide high sensitivity, fast response, wide detection range, and miniaturized design, which are suitable for hydrogen detection in complex environments. In addition, its dual-channel operational method further improves detection accuracy and environmental adaptability. This work provides technical support for safe hydrogen detection, which is suitable for hydrogen production, storage, industrial safety and environmental monitoring.